Death receptor and mitochondrial pathways are involved in germ cell apoptosis in an experimental model of autoimmune orchitis - Theas, Maria Susana (2006)
Background: Studies on experimental autoimmune orchitis (EAO) have helped to elucidate immunological mechanisms involved in testicular damage. We previously demonstrated that EAO is characterized by lymphomononuclear cell infiltrates and apoptosis of spermatocytes and spermatids expressing Fas and TNFR1. The aim of this work was to characterize the pathways involved in germ cell apoptosis in EAO and to determine the involvement of the Bcl-2 protein family in this process. Methods and Results: EAO was induced in rats by immunization with testicular homogenate (TH) and adjuvants, whereas control (C) rats were injected with saline solution and adjuvants. Testis of EAO rats showed procaspase 8 cleavage products (western blot) with high caspase 8 activity. Cytochrome c content increased in the cytosol and decreased in the mitochondrial fraction of testis from EAO rats compared with C, concomitant with increased caspase 9 activity. Bax was mainly expressed in spermatocytes and spermatids and Bcl-2 in basal germ cells (immunohistochemistry). Baxβ isoform content increased in EAO rat testis compared with C, whereas content of Baxα remained unchanged (western blot). However, Baxα content decreased in the cytosol and increased in the mitochondrial and endoplasmic reticulum (ER)-enriched fractions of testis from EAO rats compared with C (western blot). Bcl-2 content also increased in the testes of EAO rats. Conclusions: Our results demonstrated that extrinsic, mitochondrial and possibly ER pathways are inducers of germ cell apoptosis in EAO and that Bax and Bcl-2 proteins modulate this process.